Faktor-faktor penentu tahap kualiti pelaporan kewangan tahunan koperasi di Malaysia - Rusman, Ghani (2018)
The main focus of the National Cooperative Policy 2011-2020 is to ensure that the Malaysian cooperatives comply with its cooperative legislation. This study aims to determine the level of quality of annual financial reporting issued by the cooperative sector in Malaysia. Another objective of this study is to test the relationship between the characteristics of cooperatives, and its governance with the level of quality of financial reporting. The moderator variable, industry expertise was introduced to test the relationship between academic qualifications of account officers and the level of quality of financial reporting. The level of quality of financial reporting is measured using unweighted index of mandatory and voluntary information disclosure. The independent variables of cooperative characteristics tested were size, profit ratio, leverage, business type, age and year of the study, while governance variables were the board size, board members’ gender, treasurer's academic qualifications, treasurer profession and account officer’s academic qualification. The data of the study were collected through cooperative annual reports and questionaires. A total of one hundred twenty annual reports for the years 2010 and 2014 were observed. The data was analysed using multivariate regression. The results showed that the average level of financial reporting quality achieved is satisfactory. The results showed that profitability, business types and years of study had significant relationships with the level of financial reporting quality at ninety five percent confidence level. Meanwhile, cooperative size variable was significantly associated at the ninety percent confidence level. However, the results of moderating factor of the industry's expertise is not significant. The contribution of this study is to develop mandatory information disclosure level index for cooperatives in Malaysia. The index is important for measuring mandatory reporting quality among them.